2013
DOI: 10.1089/mab.2013.0038
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Antiviral Analysis of Phages That Display Peptides with an Affinity to Subunit C of Porcine Aminopeptidase

Abstract: The purified C subunit of the recombinant porcine aminopeptidase N (rpAPN-C) protein was used as an immobilized target to screen potential ligands against rpAPN-C from a 12-mer phage display random peptide library. After five rounds of biopanning, five phage clones showed specific binding affinities to rpAPN-C. In 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyl tetrazolium bromide (MTT) assays, the phage clone PM1, which contained the HDAISWTHYHPW peptide sequence, had a protective effect against TGEV infection in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Sun et al [ 101 ] reported construction and evaluation of a murine scFv library against the common receptor porcine aminopeptidase N (pAPN) of porcine coronaviruses TGEV and PEDV using the T7 phage display system [ 101 ]. Using recombinant rpAPN-C subunit and applying epitope mapping lead to identification of a peptide sequence with a potential role as a small molecular therapeutic agent against TGEV infection [ 102 ]. Identification of Neural Cell Adhesion Molecule (NCAM) as a novel interacting partner of the porcine hemagglutinating encephalomyelitis virus (PHE-CoV) using its S protein for biopanning a T7 phage display cDNA library was performed [ 103 ].…”
Section: Antibody Selection Against Coronaviruses Using Phage Displaymentioning
confidence: 99%
“…Sun et al [ 101 ] reported construction and evaluation of a murine scFv library against the common receptor porcine aminopeptidase N (pAPN) of porcine coronaviruses TGEV and PEDV using the T7 phage display system [ 101 ]. Using recombinant rpAPN-C subunit and applying epitope mapping lead to identification of a peptide sequence with a potential role as a small molecular therapeutic agent against TGEV infection [ 102 ]. Identification of Neural Cell Adhesion Molecule (NCAM) as a novel interacting partner of the porcine hemagglutinating encephalomyelitis virus (PHE-CoV) using its S protein for biopanning a T7 phage display cDNA library was performed [ 103 ].…”
Section: Antibody Selection Against Coronaviruses Using Phage Displaymentioning
confidence: 99%
“…The PEDV belongs to the genus Alphacoronavirus, in the family Coronaviridae and order Nidovirales (Belouzard et al, 2012). Previous studies have investigated various control measures to protect against PEDV infection, such as vaccines, diagnostic tools, and therapeutic drugs (Sun et al, 2008;Ren et al, 2011;Sun et al, 2012;Zhu et al, 2013;Guo et al, 2013;Kim and Lee, 2013). Various aspects of PEDV infection remain unclear, for example, swine testis (ST) cells expressing porcine aminopeptidase N of PEDV receptor were not susceptible to PEDV infection.…”
Section: Introductionmentioning
confidence: 99%